A comprehensive method of evaluating the effectiveness of the defensive operation of the operational-tactical grouping of troops at the stage of maintaining the defense line - Kryvoruchko, Ivan (Social Development and Security, 2023)
Purpose: to reveal the main provisions of the complex methodology for evaluating the effectiveness of conducting a defensive operation of an operational-tactical group of troops at the stage of holding the defense line, taking into account the enemy’s change in the direction of the main attack. Method: analysis, synthesis, mathematical modeling, operations planning method. Theoretical implications: the methodology can be used during the planning of a defensive operation and includes a partial methodology for determining the appropriate composition of forces and means of reinforcement of military units (subunits) of an operational-tactical group defending against the direction of the main attack of the enemy, which has changed, for guaranteed maintenance of the defense line within the specified time and the method of evaluating maneuver variants with a defined composition. Practical implications: the application of a complex methodology during the planning of a defensive operation will make it possible to develop well-founded recommendations for increasing the efficiency of conducting a defensive operation at the stage of holding the first line of defense of an operational-tactical group of troops, including due to the timely maneuver of determined forces and means to the threatening direction of the enemy’s attack. Papertype: methodical.